ROLE OF PRINCIPAL ON SCHOOL-BASED MANAGEMENT (SBM) AT SD NEGERI 007 PANGKALAN KERINCI - Nurhusainiwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses (1) the role of principals in implementing school-based management (SBM) and (2) the functions, strategies, and supporting and inhibiting factors in the implementation of SBM. The research is descriptive. The research subjects involved the principal, head of the school committee, and the teachers at SD Negeri 007 Pangkalan Kerinci Pelalawan. Data were collected through interview and documentation methods. Checking the validity of the data used the triangulation technique. Data were analyzed using the descriptive analysis method. The research results indicate (1) SD Negeri 007 has implemented SBM and it can be seen through its independence, either physical or non-physical independence, as well as the active participation of stakeholders. Furthermore, the results imply that (2) the dominant role of the principal in implementing SBM is the managerial role because the principal can directly choose who is in the school’s organizational structure. In addition, the result reveals that (3) the school in the context of SBM is to facilitate people in the school. The people are principals as educators, managers, administrators, supervisors, leaders, entrepreneurs, motivators, and climatologists. Lastly, (4) the inhibiting factor in implementing SBM is communication that has not been applied well in the schools and the lack of socialization for the implementation of SBM. Conversely, the supporting factor comes from the active role of school residents in the implementation of SBM and the granting of great authority or big autonomy from the office to schools.